Caracterzação espectro-temporal de cultivares de trigo por meio do índice de vegetação por diferença normalizada NDVI de sensores terrestres - Garcia, Murilo Renan (2015)
Nowadays flexibility and quality in data acquisition of yield are required to be used as a decision-maker instrument for companies and governments. The wheat crop has a very important economic social role among all the interesting economic activities in Brazil, since it has been driving feedstock of different agribusiness enterprises. Thus, the purpose on this present research was to evaluate a wheat pattern development designed for grain production by comparison of the temporal index profile of vegetation based on the normalized difference (NDVI). The profiles were acquired from 11 wheat cultivars with different phenological period, so that the most susceptible stages could be identified regarding the adverse wheather that can intervene in wheat crop yield. So. this trial was carried in two consecutive years (2013 and 2014) in Paraná state. Thereafter, according to this context, the NVDI of 11 wheat cultivars was collected in different phenological stages with GreenSeeker and FieldSpec 4 sensors that have allowed collecting the reflectance on red and the nearby infrared wave length. Periods with the highest NDVI for all cultivars occurred at 63 days in 2013, as well as at 56 and 67 days in 2014. So, it was observed that all cultivars with a middle cycle, with a longer period for leaf area formation, can reach the highest NVDI level before the earing period. The NVDI temporal profiles has shown that the wheat varieties have different behaviors in the beginning and end of the studied crop, which are mainly based in the phenological period of each cultivar.